GAMBARAN KEPATUHAN MINUM OBAT PADA PASIEN DIABETES MELITUS TIPE 2 DENGAN PENYAKIT PENYERTA HIPERTENSI DI WILAYAH KERJA PUSKESMAS SANGGAU - Yuned, Monalisa (Prodi Farmasi - Universitas Al Ghifari, 2025)
The prevalence of type 2 diabetes and hypertension comorbidity is very high,exacerbating each other and increasing the risk of complications. Medication adherence is one of the factors that determine the success of pharmacological therapy for both chronic diseases. Complex pharmacological therapy increases the risk of polypharmacy, thereby increasing the potential for Drug-Related Problems (DRPs) and often reducing medication adherence. The aim of this study is to describe the level of medication adherence in patients with type 2 diabetes and comorbid hypertension, analyze associated factors such as duration of illness, number and frequency of medication intake. This study is a descriptive analytical study with a cross-sectional design. The sample consisted of 47 patients with type 2 diabetes and hypertension. Primary data were collected using the MMAS8 questionnaire, and secondary data were obtained from medical records. The results showed that medication adherence was low in 57.4% of patients, moderate in 27.7%, and high in 14.9%. There was a significant association between medication adherence with the number of medications (p = 0.020) and medication frequency (p = 0.001), while disease duration was not significantly associated (p = 1.000). Medication adherence among patients with type 2 diabetes mellitus and hypertension was low, influenced by the number of medications and frequency of administration.